Personnel security and open source intelligence: Employing social media analytics in pre-employment screening and selection. Issue 3 (2nd July 2016) - Montaquila, Julian M.; Godwin, Cierra N.
ABSTRACT: Inarguably, social networking sites have become immensely popular. The proliferation of the type and number of social media venues are well exceeded by the quantity of data they produce. Moreover, these sites engender collateral information previously unavailable to personnel security professionals. While a recent literature review suggests this data is increasingly used in background investigations, its analysis appears devoid of any standardized protocol. The absence of any uniform procedure appears confirmed via a recent review of background investigation manuals from state peace officer accreditation organizations. As a result, specific resources, techniques, and case examples are discussed, and the federal security clearance process is provided as a recommended protocol for investigators.